Incidence of the hypothermia in neonates - P Palyzyan; N Kazemian; F Zaeri (Tehran University of Medical Sciences, 2004)
Introduction: Maintenance of the body temperature reduces mortality in low birth weight infants and adequate environmental warmth is essential for maintenance of the body temperature of newborns. However, neonatal hypothermia continues to be a significant issue in the developing countries. This study was performed to describe the incidence and severity of hypothermia after delivery. Materials and Methods: We measured body temperature of 898 consecutive newborn infants by a low-reading thermometer. Body temperature less than 36.5°C was designated as ;aposhypothermia;apos. In such cases, the infants were re-warmed according to the WHO recommendations, their body temperature was recorded every hour and their final outcome was noted. Results: The overall incidence of hypothermia was 53.2%. A total of 456 (50.2%) infants had mild hypothermia (35°C > T > 36.5° C) while 22 (2.5%) had moderate to sever hypothermia (T < 35°C). The incidence and severity of hypothermia was found to be significantly associated with birth weight (p=0.000) and gestational age (p=0.000). The duration of re-warming was also correlated with birth weight (p=0.000). Logistic regression analysis showed that the mortality rate of hypothermic neonates was 3.64 times that of the normothermic infants. The risk of death was higher in the moderate to severe hypothermic groups than in the mild hypothermic infants. Conclusion: The incidence of hypothermia was found to be high with both the incidence and severity to be significantly associated with birth weight and gestational age. The risk of death was recognized to be higher in the hypothermic newborns than non-hypothermic ones. These results show the importance of maintenance of the body temperature of newborns.